Analysis of the Impact of the Russia–Ukraine Conflict on Global Liquefied Natural Gas Shipping Network - Ranxuan Ke; Xiaoran Wang; Peng Peng (Journal of Marine Science and Engineering)
The Russia–Ukraine conflict has influenced global LNG shipping patterns; nevertheless, current research about its effects on the nodes and local regions of the LNG shipping network remains insufficient. This study employs a series of network metrics and a robustness evaluation model to examine the evolution in the structure and functionality of the LNG shipping network amid the Russia–Ukraine conflict, integrating LNG vessel origin–destination data from 2021 to 2023 to analyze the network’s structure and robustness. The research indicated that: (1) The alteration in trade relations instigated by the Russia–Ukraine conflict modified global LNG flows, resulting in a fragmented overall network structure and diminished transportation efficiency. The Russia–Ukraine conflict catalyzed the enhancement of European ports, leading to a substantial rise in the significance of premier European ports within the LNG transport network. Significant export ports, such as Ras Laffan, hold substantial importance within the network. (2) Among various assault techniques, degree-based intentional attacks inflict the greatest harm on the LNG shipping network. The robustness of the LNG shipping network declined following the Russia–Ukraine conflict, rendering it particularly susceptible in 2023. The findings indicate that the Russia–Ukraine conflict altered the structure of the LNG transportation network and diminished its robustness. The work holds substantial theoretical importance for examining the influence of geopolitical events on LNG transportation and for improving the maritime industry’s ability to navigate complicated circumstances.